Pengaruh Pendekatan Inquiry dan Discovery Terhadap Hasil Belajar Biologi Siswa Kelas XI SMA Negeri 1 Walenrang - Arsad, Bahri; Syamsiah, .; Raya, Agni (Fakultas MIPA UNM, 2011)
This research aims to find out the influence of inquiry and discovery approach toward the biology-learning outcome at grade XI students in SMA Negeri 1 Walenrang. This research was quasy experiment with Posttest Only, Non-Equivqlent Control Group Design. This research was done in SMA Negeri 1 Walenrang by taking two classes as research subjects. They were XI IPA3 as experimen group with 39 students who were tought through inquiry and discovery and XI IPA2Â with 40 students as control group who were tought through expository aproach. The data of the researh was found by giving result test after all the material had been tought. The data was analyzed showed that the result of experiment group was good categorized with average 77,26 were as result of control group was wortcing on categorized with average 71,17. Based on the test by using test data analysis t where P<0,05 so that Ho rejected and H1 was accepted. It showed that there was influence of inquiry and discovery learning approach toward the biology learning outcome at grade XI students in SMA Negeri 1 Walenrang.